(untitled) (Baltic Journal of Sport and Health Sciences, 2013)
Research backgrounds and hypothesis. This study investigates the student teachers’ preparation for the practical school placement in Poland and Kosovo. Considering the two countries with different academic backgrounds there might be reasonable differences in the state of students’ preparation to work practice. While other research concentrates on teachers’ supervision during practical placement the literature review carried out for this paper illustrates that teaching practicum, which has been a focal point of many academic discussions, has been relatively little researched, especially from the students’ perspective of the process. Understanding the differences regarding various academic systems may bring some more light into the search for the most effective ways of preparing student teachers for the school practical placement. Research aim. The purpose of the study was to analyse the student teachers’ assessments of their actual teaching competencies in order to further prepare a Cooperating PE Teachers Programme (COPET) at both universities. A sample of 154 second year Bachelor undergraduates in Poznań and 128 students from Pristina and respectively 109 from Master students from Poznań, and 45 from Master students of the international post-graduate programme in Physical Education and Sport in Kosovo were surveyed. Research method. Quantitative data were collected via the Pre-Service PE Teachers Self-Assessment Questionnaire including 25-items concerning three areas: organizational, didactic and pedagogical. A multivariate analysis of variance showed the differences between students from Poznań and Pristina. Research results. In our own research, the analysis of progression (visible in the difference between Bachelor and Master students) in their self-assessment indicates more critical self-reflection present in the assessments of students in Poznań. This was not common in the self-assessment of the students in Pristina as levels of their self- assessment at the two phases of the PETE programme (Bachelor and Master) were similar. Discussion and conclusions. Recommendations for further improvements of PETE programmes in both Polish and Kosovan Higher Education Institutions concern the introduction of a COPET programme. Improving teaching practice and professional preparedness of student teachers requires elevating the quality of academic teaching delivered to students throughout their studies. This especially concerns subjects dealing with the teaching of practical and methodological skills. Equally important is the quality of early practical experience. Keywords: PE practical school placement, student teachers’ competencies, self-assessment.